REPRODUCTIVE BIOLOGY OF THE FEMALE OF A PENABID PRAWN PARAPENAEOPSIS HARDWICKII (MIERS) - Nagabhushanam, R; Kulkarni, G K (Indian Journal of Fisheries, 2011)
Monthly records of female P. hardwickii from September 1977 to August1978 revealed that they breed throughout the year with high breeding and spawningactivity during January-May. The vertebrate male steroid hormones, testo^sterone propionate and testosterone acetate have inhibitory influence on the ovarianmaturation, whereas the aqueous extract of AG alsio blocked the Ovarian growth,but masculiniziation of the ovary was not observed. Eyestalk ablation, did notinfluence the spawning activity and the quality of eggs produced.